Body shots the effects of cosmetic surgery and diet pills on the individual's sense of self and relationships - Asutilla, Sheryl Longa 1978-
Body Shots is a qualitative study on the effects of cosmetic surgery and diet pills on the individual's sense of self and relationships. It aimed to determine the reasons and motivations of the individuals who have altered and/or enhanced themselves artificially, to know how the enhanced individuals regard the contribution of artificial enhancement processes with respect to their self-fulfillment and also, to determine the changes that occurred on the individual's interpersonal relationships. Moreover, it aimed to analyze how media acted as a vehicle in influencing its audience's concept of beauty and perception of artificial enhancement processes. The study used Albert Bandura's Social Learning Theory to demonstrate how media act as an influential model; Elaboration Likelihood Theory of Richard Petty and John Cacioppo to illustrate how an individual process information in the persuasive messages and; Cognitive Dissonance Theory of Leon Festinger to determine the distractions that occurred to an individual and the coping mechanisms used. As a multi-method study, it has employed three qualitative research methods: Focus Interview, Focus Group Discussion and Textual Analysis. The utilization of these methods executed the major findings of the study. The improvement brought about by the cosmetic surgery and diet pills among the enhanced individual is not in anyway a contribution with regard to their self-fulfillment. Some regard it merely as a physical satisfaction while some as an achievement but not to an extent of being self-fulfilled. However, it created a great change on the individual's sense of self. It is apparent that their reasons for undergoing artificial body improvements are not just what we think they do, that is wanting to become beautiful. The motivation lies deeper into their inner selves--their painstaking experiences, insecurity and excessive envy. On the other hand, it is also evident that the media played a very significant role--acting as the influential trendsetter. The media set the 'ideal' standards of beauty which, our society accepts. In effect, individuals are persuaded to conform to the standards set by the media so as not to feel unaccepted.